Study guides

☆☆

Q: What is 14p plus 14q plus p minus 7q minus 6p?

Write your answer...

Submit

Still have questions?

Related questions

Assuming you mean 7 multiplied by just 2p and assuming that p is a variable then p is calculated by: (7 * 2p) + 3 - 8 = 6p + 29 14p - 5 = 6p + 29 14p - 6p = 29 + 5 8p = 34 p = 4.25

-6p -5 = -9 +8p Add 6p to both sides: -5 = -9 + 14p Add 9 to both sides: +4 = 14p Divide both sides by 14: p =4/14 = 2/7 or 0.2857.. Are you sure that the second term in the equation was -5 and not +5 (as seems more likely)?

Factor x2 plus 12xp plus 36p2 is (x+6p)(x+6p).

algebra8p +4 = 10 +6p+8p - 6p = +10 - 42p = 6p = 3

-9p + 6p = -3p

3p + 6p = (3 + 6)p = 9p

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

6p + 12q + 18r = 6 (p + 2q + 3r)

14 + 6p = 6 + 7p 8 = p

3p

17p+17q+p-7q-6p = 12p+17q

17 + 6p = 9 6p = -8 p = -8/6 p = -4/3

8p+4=6p+10 8p-6p=2p 10+4=14 2p=14 p=7

-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r

If: 6p+3 = 8p+6 Then: p = -3/2 or -1.5

7P + 9 = 16 + 6P subtract 6P from BOTH sides P + 9 = 16 subtract 9 from both sides P = 7

6p + 11 = 35 Therefore, 6p = 35 - 11 = 24 p = 24/6 p = 4

12x+15p-6p+11x = 12x+11x+15p-6p = (12+11)x+(15-6)p = 23x + 9p

p = 4

6p + 11q + 4

6p+11q+4

The idea is to subtract 10p minus 4p.

4p+3 = -6p-5 4p+6p = -5-3 10p = -8 p = -0.8 Substituting the value of p into the original equation gives you: -1/5 = -1/5

p=1125

6p divide by 3p = 2